SCIENTIFIC AND THEORETICAL VIEWS OF POETRIC DRAMA IN RUSSIAN AND UZBEK LITERATURE - Ikramova, Aziza (Scholar Express Journals, 2021)
The article clarifies the views on poetic drama on the example of research in Russian and Uzbek literature. L.Sadykova-Gracheva, B.Alpers, A.K.Minakova, Ch.Dobrev, L.G.Prigojina, O.K.Strashkova, O.V.Jurcheva, T.O.Vlasova, D.N.Katysheva singari The nature and features of poetic drama are revealed on the basis of interpretations of Russian, M. Rakhmonov, D. Kuronov, O. Rizaev, B. Yakubov, S. Mirzaev, H. Karimov, Shuhrat Rizaev, I. Jabborov and other Uzbek scholars.
Keywords: poetic drama; lyrical drama; chronotope; genre synthesis; drama; poetic form; inner experience; romanticism; neoromantism; lyrical I